Monkeypox: Virology, Pathophysiology, Clinical Characteristics, Epidemiology, Vaccines, Diagnosis, and Treatments - Soheili, Marzieh; Nasseri, Sherko; Afraie, Maryam; Khateri, Sorour; Moradi, Yousef; Mahdavi Mortazavi, Seyede Maryam; Gilzad-Kohan, Hamed (Journal of Pharmacy & Pharmaceutical Sciences, 2022)
The World Health Organization, has declared the recent multiregional outbreak of monkeypox, a global public health emergency. Monkeypox is a zoonotic viral infection endemic to the west and central Africa. It belongs to the Poxviridae family, the Chordopoxvirinae subfamily, and the Orthopoxvirus genus. The Poxviridae family generally consists of complex, large, enveloped, and linear double-stranded DNA viruses. The initial clinical symptoms of monkeypox are often fever, severe headache, lymphadenopathy, myalgia, and fatigue. The skin lesions typically erupt within 1–3 days of the onset of fever. The rash tends to be more localized on the face and extremities than on the trunk. Monkeypox is often a self-limiting infection, and symptoms last from 2 to 4 weeks. It is isolated from various species, but the exact natural host is uncertain. Monkeypox is transmitted by close contact with infected humans or animals. Currently, no specific medication is available for monkeypox, and the existing therapeutics are the anti-viral agents approved for smallpox infection, including tecovirimat, cidofovir, and brincidofovir. Additionally, the U.S. Food and Drug Administration has approved Vaccinia Immune Globulin Intravenous for treating vaccination complications. It is diagnosed by PCR. There are currently two vaccines licensed by the U.S. Food and Drug Administration. According to the WHO guidance, the first-generation smallpox vaccines held in national reserves of some countries are not recommended as they do not meet the current safety and manufacturing standards. The interim guidance indicates that new and safer (second- and third generation) vaccines for smallpox, may be beneficial for monkeypox prevention, including JYNNEOS, which has been approved for the prevention of monkeypox. Human monkeypox was first reported in 1970. Since then, it has caused several outbreaks, mainly in central and west Africa. The first monkeypox outbreak outside of Africa occurred in the United States in 2003, linked to contact with infected pet prairie dogs. More recently (2018-2021), monkeypox cases have been reported in travelers from Nigeria to the United Kingdom, Israel, Singapore, and the US. Since May 2022, multiple monkeypox cases have been confirmed in several non-endemic countries, raising the concern of an emerging global pandemic. This review is an updated overview of our current state of knowledge regarding monkeypox virology, pathophysiology, clinical characteristics, epidemiology, vaccines, diagnosis, and treatment options.